COVID-19 Health Protocols in BRI Liga 1 : A Case Report - Wicaksono, Arif; Asyhar, Alfan Nur (Jurnal Ilmu Keolahragaan Undiksha, 2022)
Coronavirus Disease 2019 (COVID-19) pandemic had changed daily life activities including sport. Sport event usually gathered many people in sport venue that can became disease transmission. Sport events were cancelled and stop because of pandemic so did soccer. Professional athletes, teams, stakeholders, and nation worldwide were trying to restart the soccer competition in strict COVID-19 health protocols. Indonesian soccer competition known as BRI Liga 1 held a competition in strict COVID-19 health protocols during pandemic era. All people involved in competition should had fully vaccinated, follow bubble system, use face mask, use hand sanitizer, maintain distancing, and undergo COVID-19 test series. As many as 18 teams, 900 subjects were observed during 25 August 2021 to 3 October 2021. Six thousands and three hundreds PCR test and 5,400 antigen test undertaken during observation period. Health protocols used to prevent transmission and cluster caused by the competition. All athletes and team officials obey the COVID-19 health protocols so that no COVID-19 case in the time of competition. Soccer competition can be held in pandemic era using strict health protocols and can be a pilot to other sports.